TECHNOLOGY, INFORMATION, AND COMMUNICATION (ICT) LITERACY IN MATHEMATICS LEARNING IN THE DIGITAL AGE - Supardi Uki Sajiman; Huri Suhendri (Proceeding International Conference on Digital Education and Social Science, 2022)
This study aims to describe the role of technology, information, and communication (ICT) literacy in learning mathematics and identify the factors that influence ICT literacy. The research method used is a descriptive survey method. The results of the study show that : (1) ICT literacy has an important role in learning mathematics: making learning media, finding learning resources in making teaching materials, carrying out the learning process, and making learning administration, as well as assessment activities. (2) Factors that influence ICT literacy consist of: training effectiveness, visionary leadership, work-life balance, achievement motivation, facilities and infrastructure, initial capabilities, and organizational culture. The conclusions from this study: (1) ICT literacy is very important in learning mathematics. (2) The dominant factors influencing ICT literacy, namely: training effectiveness, visionary leadership, work-life balance, and achievement motivation.